Early Light-Inducible Protein (ELIP) Can Enhance Resistance to Cold-Induced Photooxidative Stress in Chlamydomonas reinhardtii - Lee, Ji Woong; Lee, Seung Hi; Han, Jong Won; Kim, Gwang Hoon (Frontiers in Physiology, 2020)
Cold weather is one of the biggest challenges in establishing a large-scale microalgae culture facility in temperate regions. In order to develop a strain that is resistant to low temperatures and still maintains high photosynthetic efficiency, transgenic studies have been conducted targeting many genes. Early light-inducible proteins (ELIPs) located in thylakoid membranes are known to protect photosynthetic machinery from various environmental stresses in higher plants. An ELIP homologue was identified from Chlamydomonas reinhardtii and named ELIP3. The role of the gene was analyzed in terms of photosynthetic CO2 assimilation under cold stress. Western blot results showed a significant accumulation of ELIP3 when the cells were exposed to cold stress (4℃). High light stress alone did not induce the accumulation of the protein. Enhanced expression of ELIP3 helped survival of the cell under photo-oxidative stress. The influx of CO2 to the photobioreactor induced strong accumulation of ELIP3, and enhanced survival of the cell under high light and cold stress. When the oxidative stress was reduced by adding a ROS quencher, TEMPOL, to the media the expression of ELIP3 was reduced. A knockdown mutant showed much lower photosynthetic efficiency than wild type in low temperature, and died rapidly when it was exposed to high light and cold stress. The overexpression mutant survived significantly longer in the same conditions. Interestingly, knockdown mutants showed negative phototaxis, while the overexpression mutant showed positive phototaxis. These results suggest that ELIP3 may be involved in the regulation of the redox state of the cell and takes important role in protecting the photosystem under photooxidative stress in low temperatures.